Network Diagrams as a Means of Comparing Spelling Systems - Vaňková, Marie (Neuphilologische Mitteilungen, 2023)
The purpose of the paper is to explore the possibilities of using network diagrams as a means of analysing spelling systems of early Middle English texts. The diagrams are available in a recently constructed electronic tool based on the Linguistic Atlas of Early Middle English (LAEME), which means that their applicability to actual analyses has not yet been properly assessed. The tool can visualise connections between letters and digraphs which are used interchangeably or the correspondences between two letters (digraphs) found in two different texts. The paper draws on a comparison of the texts in two selected manuscripts available in LAEME (Lambeth 487 and Trinity B.14.52). The study focuses mainly on the differences, similarities and connections between the individual spelling systems. The results show, which tasks are relatively easy to perform using the diagrams and what are the chief drawbacks of the proposed method.